Students’ behavioural intention toward online learning during covid-19 pandemic: A case among UUM students - Saif Kareem, Abdul Abbas Khikani (2021)
People all across the globe were affected by Covid-19, commonly known as coronavirus disease, which was responsible for an outbreak of respiratory sickness. The Covid-19 epidemic has affected a large number of people, including students enrolled in higher education institutions such as universities. Students had a variety of challenges due to the unexpected transition from traditional teaching to online learning, including difficulties in their educational experiences in the learning process. This study seeks to examine the factors that influence the use of online learning during the period of Covid-19. A purely quantitative research design was adapted to analyse the data gathered from 105 participants from university Utara Malaysia to answer 19 items questionnaire adapted from (Venkatesh, 2013). In order to test the hypotheses, Microsoft Excel 16 and SmartPLS version 3.0 was used. The findings indicate that performance expectancy, effort expectancy, and social influence significantly correlate with students’ behavioural intention. In contrast, facilitating condition has not been found to be significant to students’ behavioural intention. Finally, the partial inconsistency in this research study’s findings compared to previous literature highlights the importance of future research investigating students online learning during Covid-19.